PELAYANAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL DI KABUPATEN KONAWE TAHUN 2017 (BERDASARKAN UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN) - Hasjad, Hasjad (Aksara Public, 2019)
This research is entitled the Birth Certificate Service at the Population and Civil Registry Service in Konawe Regency in 2017 (Based on Law Number 24 of 2013 concerning Population Administration) against the background of public services or general forms of all services, both in the form of public goods and public services. which in principle is the responsibility and carried out by the relevant institutions, in the context of efforts to meet the needs of the community and in the context of implementing the provisions of the legislation. The type and method of research used is a type of descriptive research, which can be interpreted as a problem-solving process investigated by describing or describing the state of the subject and object of research at present based on the facts that appear or how they are. While the method used is a qualitative research method by describing the actual situation in detail and actual by looking at the problem and the purpose of the study. The results of this study indicate that the services of birth certificates at the Population and Civil Registry Service in Konawe Regency in 2017 based on Law Number 24 of 2013 concerning Population Administration are still lacking in inadequate facilities. From the government side, it can be concluded that there are still obstacles faced by the government that manage the issuance of E-KTP and birth certificates. So that the E-KTP ownership and birth certificates in Konawe District are still very low.